A novel method for predicting perineural invasion of distal cholangiocarcinoma on multidetector-row computed tomography - Yamamoto, Ryusei; Sugiura, Teiichi; Okamura, Yukiyasu; Ashida, Ryo; Ohgi, Katsuhisa; Yamada, Mihoko; Otsuka, Shimpei; Aramaki, Takeshi; Asakura, Koiku; Uesaka, Katsuhiko (Surgery Today, 2022)
Purpose Excessive perineural invasion (PNI) is associated with a high risk of radial margin (RM) positivity and a poor prognosis for patients with distal cholangiocarcinoma (DCC). This study evaluates a new method of predicting the extent of PNI preoperatively. Methods The subjects of this retrospective study were 201 patients who underwent resection for DCC between 2002 and 2018. This study identified the ‘periductal enation sign’ (PES), defined as the surrounding soft tissue enhancement that appears as an enation from the circumference of the enhanced extrahepatic bile duct on multidetector-row computed tomography (MDCT) scans, as a predictor of PNI. We analyzed the outcomes of the patients in relation to the presence or absence of the PES on MDCT scans. Results The PES in the PNI-positive group was significantly longer than that in the PNI-negative group. As the length of the PES extended, the grade of PNI increased. A positive PES was defined as a PES length of ≥ 2.0 mm. Patients with a positive PES were more frequently positive for RM (23.7% vs. 2.1%) and locoregional recurrence (23.7% vs. 6.3%) and exhibited significantly poorer overall survival than those with a negative PES (30.2% vs. 54.6% at 5 years). Conclusions The presence and extent of PNI can be predicted easily and effectively by the PES length. A positive PES was associated with poor local controllability and a poor prognosis.